Composite catalyst as well as preparation method and application thereof

By precipitating nickel and additive metal precursors in situ on the support surface, a composite catalyst with high catalytic activity and selectivity was prepared, which solved the problems of high catalyst cost, poor activity and discontinuity in the prior art, and achieved efficient and economical catalytic hydrogenation reaction.

CN119680558APending Publication Date: 2025-03-25SHANGHAI RES INST OF CHEM IND CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411872507.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The catalysts used in the catalytic hydrogenation of ethylenically unsaturated carboxylic acids/anhydrides for the preparation of corresponding saturated carboxylic acids/anhydrides have problems such as high prices for precious metals, poor catalytic activity of transition elements, and difficult process to achieve continuous production and catalyst recovery.

Method used

By using a method of preparing a composite catalyst, a catalyst with uniform dispersion of highly active components is obtained by mixing a support, a nickel precursor and an additive metal precursor in a specific solvent, and performing in situ precipitation and heat treatment.

Benefits of technology

An efficient catalytic hydrogenation reaction was achieved, with a raw material conversion rate greater than 91%, a target product selectivity ≥98.4%, and a simple process and low cost, which is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680558A_ABST
    Figure CN119680558A_ABST
Patent Text Reader

Abstract

The invention provides a composite catalyst as well as a preparation method and application thereof. The preparation method of the catalyst comprises the following steps: dispersing a carrier in a first solvent to form slurry; dissolving a nickel precursor and an optional auxiliary metal precursor in a second solvent to form a precursor solution; mixing the slurry and the precursor solution to form a mixed material; adding an alkaline precipitator into the mixed material to obtain a catalyst precursor; and carrying out heat treatment and reduction on the catalyst precursor to obtain the composite catalyst. According to the catalyst disclosed by the invention, high-cost noble metal is not used, and extremely excellent raw material conversion rate and target product selectivity can be realized under relatively mild reaction conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalysis, and more specifically to a supported composite catalyst and a preparation method thereof, and also to the use of the catalyst in catalytic hydrogenation of ethylenically unsaturated carboxylic acids / anhydrides to prepare corresponding saturated carboxylic acids / anhydrides. Background Art

[0002] Ethylenically unsaturated carboxylic acid / anhydride refers to a carboxylic acid / anhydride compound containing at least one carbon-carbon unsaturated double bond in the molecule, and has extremely wide applications in various fields. For example, as a typical representative, maleic acid / maleic anhydride (also referred to as maleic acid / maleic anhydride) is extremely commonly used in catalytic hydrogenation to prepare succinic acid or succinic anhydride, which is an important organic synthesis intermediate and fine chemical raw material, and has a wide range of applications in pesticides, medicines, petrochemicals, dyes and alkyd resins, and especially its derivatives (biodegradable plastics PBS, etc.) are fine chemical products with high added value. For example, succinic anhydride / succinic acid and butanediol polycondensation can produce excellent biodegradable plastics polybutylene succinate (PBS). With the increasing severity of the white pollution problem and the increasingly stringent environmental protection regulations for chemical production and daily products worldwide, the market prospects of biodegradable plastics PBS are very broad, thereby greatly stimulating and driving the market demand for upstream products succinic anhydride and succinic acid. The most competitive production route is to synthesize succinic anhydride by catalytic hydrogenation using maleic anhydride as raw material. However, this synthesis route still has serious defects that need to be solved urgently.

[0003] Specifically, the catalyst used for the above-mentioned hydrogenation catalytic reaction in the prior art is always unsatisfactory. The most commonly used catalyst at present is a catalyst based on precious metals. Although it has excellent catalytic performance, the high price of precious metal elements seriously limits the practicality of such catalysts in industrial-scale production. For this reason, previous research attempts to replace precious metal elements with relatively cheap transition elements to prepare catalysts, but these catalysts based on transition elements often have the problem of poor catalytic activity, and all need to adopt higher reaction temperature and reaction pressure (hydrogen pressure) during hydrogenation catalytic reaction, and even if more harsh reaction conditions are adopted, it is still impossible to achieve the same excellent raw material (such as maleic acid / anhydride) conversion rate and target product (such as succinic acid / succinic anhydride) selectivity as precious metal catalysts.

[0004] Another drawback of the prior art is that, due to various limitations, the prior art process often has to use an autoclave reactor to carry out the reaction in an intermittent manner and cannot be produced in a continuous manner, which seriously limits the improvement of the process output.

[0005] The third defect of the prior art is that the process of the prior art is often unable to effectively recycle and reuse the catalyst, which further increases the process cost. In order to overcome this problem, the prior art attempts to prepare the catalyst by impregnation or coprecipitation, but in the catalysts prepared by these methods (especially the impregnation method), the active components are often easy to agglomerate on the catalyst surface, seriously affecting the dispersion and utilization of the metal active components. Limited by the solubility and dispersibility of the metal precursor, a single impregnation operation is difficult to achieve the required high active component content (for example, higher than 20% by weight) in the catalyst. If the wording operation is adopted, the cost will be further increased due to the cumbersome steps. The coprecipitation method needs to consider many factors. Factors such as the type of reactants, the order of addition, the precipitation pH, and the precipitation temperature will have a great influence on the precipitation reaction, especially the selection of the carrier and the active component will have a great influence on the prepared product. Therefore, how to achieve a high content of uniform dispersion of active components in the preparation process of the hydrogenation catalyst so that the catalyst has higher hydrogenation activity and stability is a problem to be solved.

[0006] In order to overcome the above problems, people have invested a lot of scientific research costs and human resources, trying to improve the catalyst formula and preparation process, or optimize the reaction process, but have not been able to obtain satisfactory catalytic effects.

[0007] Therefore, there is an urgent need in the art to develop a new technology for catalytic hydrogenation of ethylenically unsaturated carboxylic acids / anhydrides to prepare corresponding saturated carboxylic acids, which needs to be able to achieve excellent catalytic performance, especially high feedstock conversion rate and target product selectivity, with simple process design and low cost, and preferably also be able to overcome the problems related to process continuity and catalyst synthesis.

[0008] In view of the above problems in the prior art, the inventors of the present application have conducted a lot of in-depth research and developed a novel technology to effectively solve the above problems in the prior art. Summary of the invention

[0009] A first aspect of the present invention provides a method for preparing a composite catalyst, the method comprising:

[0010] Step 1: dispersing the carrier in a first solvent to form a slurry;

[0011] Step 2: dissolving a nickel precursor and an optional auxiliary metal precursor in a second solvent to form a precursor solution;

[0012] Step 3: mixing the slurry and the precursor solution to form a mixed material;

[0013] Step 4: adding an alkaline precipitant to the mixed material to obtain a catalyst precursor;

[0014] Step 5: heat-treating and reducing the catalyst precursor to obtain the composite catalyst;

[0015] The nickel precursor is a water-soluble salt of nickel;

[0016] The auxiliary metal precursor is a water-soluble salt of one or more elements selected from the group consisting of Group II alkaline earth metals, Group IB elements, Group IIB elements, Group VIB elements, Group VIII transition metals, and rare earth metals.

[0017] According to an embodiment of the first aspect of the present application, in step 1, the first solvent is water or a water-containing solvent. According to another embodiment of the first aspect of the present application, in step 1, the carrier is alumina powder. According to another embodiment of the first aspect of the present application, in step 1, based on the total weight of the slurry, the content of the carrier in the slurry is 18-40% by weight.

[0018] According to another embodiment of the first aspect of the present application, in the step 2, the second solvent is water or an aqueous solvent. According to another embodiment of the first aspect of the present application, in the step 2, the concentration of nickel ions in the precursor solution is 0.1-2.5 mol / L. According to another embodiment of the first aspect of the present application, in the step 2, when the precursor solution contains an auxiliary metal precursor, the content of the auxiliary metal precursor in the precursor solution is 0.1 wt% to 0.8 wt% based on the total weight of the precursor solution.

[0019] According to another embodiment of the first aspect of the present application, in the step 2, the auxiliary metal is selected from one or more of the following: Mg, Cu, Zn, Mo, W, Co, La, and Ce.

[0020] According to another embodiment of the first aspect of the present application, in the step three, the slurry and the precursor solution are mixed in a weight ratio of 1:3 to 4:1.

[0021] According to another embodiment of the first aspect of the present application, in the step four, the alkaline precipitant is selected from one or more of the following: alkali metal carbonates, alkali metal bicarbonates, alkali metal hydroxides, ammonium carbonate, ammonium bicarbonate, and ammonium hydroxide.

[0022] According to another embodiment of the first aspect of the present application, the heat treatment of the catalyst precursor includes drying at a temperature of 90-150° C. for 1-12 hours and calcining at a temperature of 450-600° C. for 1-6 hours.

[0023] According to another embodiment of the first aspect of the present application, the reduction includes reduction at a temperature of 350-600°C for 1-8 hours, and a reducing gas and / or an inert gas is used during the reduction process, and the reducing gas is selected from hydrogen, carbon monoxide or a combination thereof; the inert gas is selected from nitrogen, argon, or a combination thereof.

[0024] The second aspect of the present invention provides a composite catalyst, which is prepared by the method of any embodiment of the first aspect of the present application.

[0025] According to an embodiment of the second aspect of the present application, the composite catalyst comprises a carrier, nickel and an optional promoter metal. According to another embodiment of the second aspect of the present application, the content of the nickel is 15-40 parts by weight, calculated as nickel oxide, based on the weight of the carrier as 100 parts by weight. According to another embodiment of the second aspect of the present application, in the case where the composite catalyst contains a promoter metal, the content of the promoter metal is 0.1-5 parts by weight, calculated as oxide, based on the weight of the carrier as 100 parts by weight.

[0026] The third aspect of the present invention provides a method for performing a catalytic hydrogenation reaction, which comprises performing a catalytic hydrogenation reaction on an unsaturated carboxylic acid or its anhydride containing a carbon-carbon unsaturated double bond in the presence of a catalyst to prepare a saturated carboxylic acid or its anhydride, wherein the catalyst is a composite catalyst of any one embodiment of the second aspect of the present application.

[0027] According to one embodiment of the third aspect of the present application, the unsaturated carboxylic acid or its anhydride containing a carbon-carbon unsaturated double bond is maleic acid or maleic anhydride, and the saturated carboxylic acid or its anhydride is succinic acid or succinic anhydride.

[0028] According to another embodiment of the third aspect of the present application, the catalytic hydrogenation reaction is carried out at a temperature of 60-100°C.

[0029] According to another embodiment of the third aspect of the present application, the feedstock conversion rate of the catalytic reaction is greater than 91%, and the target product selectivity is ≥98.4%.

[0030] In the specific implementation section below, the method and prepared product of the present application are further introduced in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1A and Figure 1B A schematic diagram of a maleic anhydride / maleic acid catalytic hydrogenation reaction according to an exemplary embodiment of the present application is shown.

[0032] Figure 2The XRD spectra of the catalysts prepared in Example 1 and Comparative Examples 1-2 are shown.

[0033] Figure 3 The H2-TPR spectra of the catalysts prepared in Example 1 and Comparative Examples 1-2 are shown.

[0034] Figure 4 The XRD spectra of the catalysts prepared in Example 2 and Comparative Examples 3-4 are shown. DETAILED DESCRIPTION

[0035] "Range" disclosed herein is in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, a range of 60-120 and 80-110 is listed for a particular parameter, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0036] In this application, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.

[0037] In this application, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0038] In this application, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0039] In this application, if there is no special explanation, the "including" mentioned herein means open or closed. For example, the "including" may mean that other components not listed may also be included, or only the listed components may be included.

[0040] The composite catalyst of the present application can be prepared by a method comprising the following steps:

[0041] Step 1: Disperse the carrier in the first solvent to form a slurry, wherein the specific surface area of ​​the carrier is 200-320m 2 / g, pore volume 0.5-1.2cm3 / g, average pore size 5-20nm;

[0042] Step 2: dissolving a nickel precursor and an optional auxiliary metal precursor in a second solvent to form a precursor solution;

[0043] Step 3: mixing the slurry and the precursor solution to form a mixed material;

[0044] Step 4: adding an alkaline precipitant to the mixed material to obtain a catalyst precursor;

[0045] Step 5: heat-treating and reducing the catalyst precursor to obtain the composite catalyst.

[0046] According to one embodiment of the present application, the carrier used in step 1 is an alumina carrier, and the specific surface area of ​​the alumina carrier is 220-280 m 2 / g, pore volume is 0.5-0.8 cm 3 / g, with an average pore size of 6-12 nanometers. According to a preferred embodiment of the present application, the specific surface area of ​​the pseudo-boehmite is 240-280 m 2 / g, pore volume is 0.50-0.70 cm 3 / g, average pore size 7-11 nanometers.

[0047] According to another embodiment of the present application, the first solvent used in step 1 includes water or an aqueous solvent, the aqueous solvent refers to a mixture of water and an organic solvent, the organic solvent includes methanol, ethanol, methyl ether, ethyl ether, acetone, methyl formate, ethyl acetate, or any combination thereof. Preferably, the first solvent is water, such as deionized water.

[0048] According to another embodiment of the present application, based on the total weight of the slurry, the content of the carrier in the slurry is 18-40% by weight, preferably 20-27% by weight.

[0049] According to another embodiment of the present application, the nickel precursor used in step 2 is a water-soluble salt of nickel, such as nickel nitrate, nickel sulfate, nickel chloride, nickel phosphate, nickel formate, nickel acetate, nickel oxalate, methoxy nickel, ethoxy nickel, etc., and the water-soluble salt of nickel may contain crystal water or may not contain crystal water. Preferably, the nickel precursor is selected from one or more of the following: nickel nitrate, nickel sulfate, nickel chloride, nickel formate, nickel acetate, nickel oxalate, nickel nitrate hexahydrate, nickel sulfate heptahydrate, nickel acetate tetrahydrate, nickel oxalate dihydrate, nickel chloride hexahydrate.

[0050] According to another embodiment of the present application, the concentration of nickel ions in the precursor solution is 0.1-2.5 mol / L, or 0.5-2.0 mol / L, or 0.8-1.5 mol / L, or 1.0-1.2 mol / L.

[0051] The auxiliary metal precursor is an optional component, that is, the precursor solution may or may not contain the auxiliary metal precursor.

[0052] According to another embodiment of the present application, in the case where the precursor solution contains an auxiliary metal precursor, the auxiliary metal precursor used in step 2 is selected from water-soluble salts of one or more of the following elements: alkaline earth metals of group II, elements of group IB, elements of group IIB, elements of group VIB, transition metals of group VIII, and rare earth metals, preferably selected from water-soluble salts of one or more of the following elements: Mg, Cu, Zn, Mo, W, Co, La, Ce. The auxiliary metal precursor may include water-soluble salts of one or more of the following types: nitrates, sulfates, hydrogen sulfates, phosphates, hydrogen phosphates, dihydrogen phosphates, hydrochlorides (chlorides), formates, acetates, and oxalates.

[0053] According to another embodiment of the present application, in the case where the precursor solution contains an auxiliary metal precursor, the content of the auxiliary metal precursor is 0.1 wt % to 0.8 wt % based on the total weight of the precursor solution; or 0.2 wt % to 0.6 wt %; or 0.25 wt % to 0.5 wt %; or 0.3 wt % to 0.4 wt %.

[0054] According to another embodiment of the present application, the second solvent used in step 2 includes water or an aqueous solvent, the aqueous solvent refers to a mixture of water and an organic solvent, the organic solvent includes methanol, ethanol, methyl ether, ethyl ether, acetone, methyl formate, ethyl acetate, or any combination thereof. Preferably, the first solvent is water, such as deionized water.

[0055] According to another embodiment of the present application, in the step three, the slurry prepared in the step one and the precursor solution prepared in the step two are mixed in a weight ratio of 1:3 to 4:1 to form a mixed material. For example, the weight ratio of the two can be 1:2 to 3:1, or 1:1.5 to 2:1, or 1:1 to 1.5:1.

[0056] According to another embodiment of the present application, in the step 4, the alkaline precipitant is formulated into an alkaline reagent solution, and then the alkaline reagent solution is added to the mixed material obtained in the step 3 in a dropwise manner under stirring conditions, and a catalyst precursor is obtained by an in-situ precipitation reaction. According to one embodiment of the present application, the pH value of the entire system is controlled at 7.5-8.0 by adding the alkaline reagent solution to the mixed material obtained in the step 3. According to another embodiment of the present application, the precipitation reaction duration is 30 minutes to 4 hours, preferably 40 minutes to 3 hours, and more preferably 1-2 hours. According to another embodiment of the present application, after the precipitation is completed, the entire system is continued for 1-6 hours, preferably 2-5 hours, and more preferably 2.5-3 hours, for aging treatment. According to another embodiment, after the aging treatment, the obtained material is subjected to solid-liquid separation, such as solid-liquid separation by filtration, centrifugation or decanting, and then the solid is washed, such as ethylene with deionized water until the solid is neutral, thereby obtaining a catalyst precursor. According to another embodiment of the present application, the alkaline precipitant is selected from one or more of the following: alkali metal carbonates, alkali metal bicarbonates, alkali metal hydroxides, ammonium carbonate, ammonium bicarbonate, ammonium hydroxide; preferably, the alkaline precipitant is sodium carbonate or sodium bicarbonate. The concentration of the alkaline precipitant solution is not important and may need to be appropriately selected.

[0057] According to another embodiment of the present application, in step five, the catalyst precursor obtained in step four is subjected to heat treatment and reduction to obtain the composite catalyst. According to another embodiment of the present application, the heat treatment includes drying at a temperature of 90-150°C for 1-12 hours, for example, the drying temperature may be 100-140°C, preferably 120-130°C, and the drying time may be 2-10 hours, or 4-8 hours, or 6-7 hours. According to another embodiment of the present application, the heat treatment also includes, after the above-mentioned drying, calcining at a temperature of 450-600°C for 1-6 hours, for example, the calcining temperature may be 350-600°C, preferably 400-550°C, more preferably 450-500°C, and the duration of calcination may be 1-8 hours, for example, 2-6 hours, or 3-5 hours.

[0058] According to one embodiment of the present application, the catalyst precursor is reduced after the heat treatment, for example, the reduction comprises heating at a temperature of 350-600°C for 1-8 hours in the presence of a reducing gas and / or an inert gas, the temperature of the reduction step is preferably 400-550°C, more preferably 450-500°C, and the duration of the reduction step may be 2-6 hours, preferably 3-4 hours. The reducing gas used in the reduction step is selected from hydrogen, carbon monoxide, or a combination thereof; preferably hydrogen. The inert gas used in the reduction step is selected from nitrogen, argon, or a combination thereof; preferably nitrogen.

[0059] According to a non-limiting embodiment of the present application, in the catalyst obtained after the above reduction treatment, the nickel element and the promoter metal are at least partially reduced to zero valence, preferably most of them are reduced to zero valence.

[0060] According to an exemplary embodiment of the present application, the method of the present invention is carried out in the following manner: adding a carrier to deionized water and stirring thoroughly to form a slurry; preparing a mixed salt solution from a soluble salt of a precursor of the active component nickel and a soluble salt of a precursor of an optional auxiliary metal; slowly adding the mixed salt solution to the slurry under stirring conditions; preparing an alkaline precipitant into a solution; adding the alkaline precipitant solution to the mixture of the mixed salt solution and the slurry in a dropwise manner under stirring conditions, and controlling the precipitation endpoint pH value as described above; after the alkaline precipitant solution is added dropwise, stirring and aging are performed; filtering and washing the aged material until the filtrate is neutral, and drying, roasting, and grinding the filter cake to obtain a nickel-based catalyst precursor; the catalyst precursor is reduced in hydrogen or in a mixed gas of hydrogen and nitrogen under heating conditions to obtain a catalyst.

[0061] According to another embodiment of the present application, in the catalyst of the present invention, based on the mass of the carrier contained in the catalyst as 100 parts by mass, the mass of the nickel active component contained in the catalyst as oxide (nickel oxide) is 15-40 parts, and the mass of the auxiliary agent as oxide is 0.1-5 parts.

[0062] The method of the present invention is characterized in that during the preparation process, the formation and deposition of active components occur simultaneously, and the active components are grown by in-situ precipitation on the surface of a specific carrier, thereby accurately preparing a catalyst with a specific microstructure and performance, thereby achieving excellent reaction performance.

[0063] According to one embodiment of the application, the catalyst of the present invention is very suitable for the catalytic hydrogenation reaction of ethylenically unsaturated carboxylic acid or anhydride containing at least one carbon-carbon double bond, to synthesize the corresponding saturated carboxylic acid / anhydride product. For example, the ethylenically unsaturated carboxylic acid / anhydride containing at least one carbon-carbon double bond can be a C3-C16 carboxylic acid / anhydride containing one, two or three carbon-carbon double bonds and one or two carboxyl groups, such as a C3-C12 carboxylic acid / anhydride containing one or two carbon-carbon double bonds and one or two carboxyl groups, or a C3-C8 carboxylic acid / anhydride containing one carbon-carbon double bond and one or two carboxyl groups. Preferably, the reaction raw material is maleic acid or maleic anhydride, and catalytic hydrogenation produces succinic acid or succinic anhydride.

[0064] For example Figure 1A and Figure 1B The invention shows that the catalyst of the present invention is used to catalyze the hydrogenation reaction of maleic acid or maleic anhydride to prepare the desired succinic acid or succinic anhydride.

[0065] The present invention can achieve the following advantages:

[0066] 1. The method of the present invention prepares the catalyst by an in-situ loading method, which is easy to operate, simple in process, good in repeatability, easy to scale up industrially, and has higher competitiveness.

[0067] 2. The in-situ loading method of the present invention avoids the problems of uneven active components and low dispersion caused by other preparation methods.

[0068] 3. The catalyst prepared by the method of the present invention has a specially designed microstructure, which has an excellent effect on its catalytic performance.

[0069] 4. The catalyst prepared by the present invention can achieve excellent catalytic activity for catalytic hydrogenation of olefinic unsaturated olefins. For example, when the catalyst is used for catalytic hydrogenation of maleic anhydride, the conversion rate of maleic anhydride is greater than 91%, preferably up to 99.9%, and the selectivity of succinic anhydride is higher than 98.4%, preferably up to 99.6%.

[0070] In the following examples, the method of the present application is specifically described with specific examples, the purpose of which is to better understand the content of the present application. It should be understood that these examples are merely illustrative and not restrictive.

[0071] Example

[0072] The alumina used in the following examples is alumina of different models and specifications purchased from Shandong Aluminum Company. Before the experiment, its microstructure (specific surface area, total pore volume, average pore size) was characterized by BET, and the alumina with the microstructure was used in each example and comparative example respectively; the other reagents used were all commercially available analytical pure reagents, and the water used was deionized water.

[0073] Example 1

[0074] In this example, the catalyst was synthesized by the following steps.

[0075] Weigh 55.89 g of alumina (specific surface area 240 m 2 / g, with a total pore volume of 0.65 cm 3 / g, average pore size of 11.0nm), mixed with 200ml of ionized water, and stirred thoroughly to form a uniform slurry.

[0076] 58.16 g of nickel nitrate hexahydrate and 0.94 g of lanthanum nitrate hexahydrate were weighed and dissolved in 200 ml of deionized water to prepare a mixed salt water solution of nickel nitrate and lanthanum nitrate.

[0077] Weigh 25.86 g of anhydrous sodium carbonate and dissolve it in deionized water to prepare a sodium carbonate aqueous solution with a concentration of 1.2 mol / L.

[0078] The slurry was added to the reactor, stirring was started, and the reactor was heated to 50°C while stirring at a speed of 300 rpm. While maintaining the stirring and heating, the mixed salt solution was slowly added to the reactor, and then the sodium carbonate aqueous solution was gradually added dropwise to the reactor to perform an in-situ precipitation reaction for 60 minutes. The precipitation pH was adjusted to 7.5-8.0. After the precipitation was completed, the materials in the reactor were stirred for 3 hours at the above temperature and stirring speed for aging treatment.

[0079] Then stop stirring, filter the material in the reactor, and wash the solid material with deionized water until the washing liquid is neutral. Place the filter cake in an oven, dry it at 120°C for 6 hours, and then put it into a muffle furnace and roast it at 500°C for 3 hours. Grind the solid after roasting to obtain a catalyst precursor. The catalyst precursor is placed in a fixed bed reactor, and a hydrogen and nitrogen mixed gas (mixed volume ratio 1:1) is introduced therein, and the temperature is slowly heated to 450°C by program heating, and heating reduction is continued for 4 hours to obtain the catalyst of Example 1.

[0080] The XRD spectrum of the catalyst prepared in Example 1 is as follows: Figure 2As shown, no characteristic diffraction peak of nickel oxide is observed, indicating that in the catalyst, the nickel-containing component is highly uniformly dispersed on the carrier and there is no local aggregation phenomenon.

[0081] Example 2

[0082] In this example, the catalyst was synthesized by the following steps.

[0083] Weigh 55.89 g of alumina (specific surface area 280 m 2 / g, with a total pore volume of 0.50 cm 3 / g, average pore size of 7.2nm), mixed with 200 ml of ionized water, and stirred thoroughly to form a uniform slurry.

[0084] 58.16 g of nickel nitrate hexahydrate was weighed and dissolved in deionized water to prepare a 1 mol / L nickel nitrate aqueous solution.

[0085] Weigh 25.44 g of anhydrous sodium carbonate and dissolve it in deionized water to prepare a sodium carbonate aqueous solution with a concentration of 1.2 mol / L.

[0086] The slurry was added to the reactor, stirring was started, and the reactor was heated to 50°C while stirring at a speed of 300 rpm. While maintaining the above stirring and heating, the nickel nitrate aqueous solution was slowly added to the reactor, and then the sodium carbonate aqueous solution was gradually added dropwise to the reactor to perform an in-situ precipitation reaction for 60 minutes. The precipitation pH value was adjusted to 7.5-8.0. After the precipitation was completed, the material in the reactor was stirred for 3 hours at the above temperature and stirring speed for aging treatment.

[0087] Then stop stirring, filter the material in the reactor, and wash the solid material with deionized water until the washing liquid is neutral. Place the filter cake in an oven, dry it at 120°C for 6 hours, and then put it into a muffle furnace and roast it at 500°C for 3 hours. Grind the solid after roasting to obtain a catalyst precursor. The catalyst precursor is placed in a fixed bed reactor, and a hydrogen and nitrogen mixed gas (mixed volume ratio 1:1) is introduced therein, and the temperature is slowly heated to 450°C by program heating, and heating reduction is continued for 4 hours to obtain the catalyst of Example 2.

[0088] The XRD spectrum of the catalyst prepared in Example 2 is as follows: Figure 3 As shown, no characteristic diffraction peak of nickel oxide is observed, indicating that in the catalyst, the nickel-containing component is highly uniformly dispersed on the carrier and there is no local aggregation phenomenon.

[0089] Comparative Example 1

[0090] In this comparative example, the catalyst was synthesized by the prior art isovolumetric impregnation method.

[0091] Weigh 58.16 g of nickel nitrate hexahydrate and dissolve it in deionized water to prepare a 1 mol / L nickel nitrate aqueous solution. Weigh 55.86 g of aluminum oxide (specific surface area 250 m 2 / g, total pore volume of 0.75cc / g, average pore size of 12nm), mixed with the above nickel nitrate solution, stirred evenly and left to stand for four hours, then transferred the container containing all the liquid and solid to a constant temperature oven, dried at 120°C for 6 hours, and then placed in a muffle furnace and roasted at 500°C for 3 hours. The solid after roasting was ground to obtain a catalyst precursor. The catalyst precursor was placed in a fixed bed reactor, hydrogen and nitrogen mixed gas (mixing volume ratio 1:1) was introduced therein, and then heated to 450°C, and continued to heat and reduce for 4 hours to obtain the catalyst of Comparative Example 1.

[0092] The XRD spectrum of the catalyst prepared in Comparative Example 1 is as follows: Figure 2 As shown, obvious characteristic diffraction peaks of nickel oxide are observed, indicating that in this catalyst, the nickel-containing component has undergone local aggregation on the support.

[0093] Comparative Example 2

[0094] In this comparative example, the catalyst was synthesized by the co-precipitation method of the prior art without using a carrier.

[0095] 12.00 g of nickel nitrate hexahydrate and 113.10 g of aluminum nitrate nonahydrate were weighed and dissolved in 300 ml of deionized water to prepare a mixed salt solution.

[0096] Weigh 62.78 g of anhydrous sodium carbonate and dissolve it in deionized water to prepare a sodium carbonate aqueous solution with a concentration of 2.0 mol / L.

[0097] The mixed salt solution was added to the reactor, stirring was started, and the reactor was heated to 50° C. while stirring at a speed of 300 rpm. While maintaining the stirring and heating, the sodium carbonate aqueous solution was gradually added dropwise to the reactor to perform an in-situ precipitation reaction for 60 minutes. The precipitation pH value was adjusted to 7.5-8.0. After the precipitation was completed, the material in the reactor was stirred for 3 hours at the above temperature and stirring speed for aging treatment.

[0098] Then stop stirring, filter the material in the reactor, and wash the solid material with deionized water until the washing liquid is neutral. Place the filter cake in an oven, dry it at 120°C for 6 hours, and then put it into a muffle furnace and roast it at 500°C for 3 hours. Grind the solid after roasting to obtain a catalyst precursor. The catalyst precursor is placed in a fixed bed reactor, and a hydrogen and nitrogen mixed gas (mixed volume ratio 1:1) is introduced therein, and the temperature is slowly heated to 600°C by program heating, and heating reduction is continued for 4 hours to obtain the catalyst of Comparative Example 2.

[0099] The XRD spectrum of the catalyst prepared in Comparative Example 2 is as follows: Figure 2 As shown in Figure 2, no obvious characteristic diffraction peaks of nickel oxide were observed, but the H2-TPR spectrum of the catalyst was Figure 3 It shows that the reduction temperature is significantly higher than that of Example 1 and Comparative Example 1. Such a high reduction temperature will also lead to local aggregation of nickel components.

[0100] Comparative Example 3

[0101] In this comparative example, the catalyst was synthesized by the following steps, wherein the carrier microstructure used did not meet the definition of the present application.

[0102] Weigh 55.89 g of alumina (specific surface area 315 m 2 / g, total pore volume of 0.23cc / g, average pore diameter of 3.0nm), mixed with 100ml of ionized water, and stirred thoroughly to form a uniform slurry.

[0103] 58.16 g of nickel nitrate hexahydrate was weighed and dissolved in deionized water to prepare a 1 mol / L nickel nitrate aqueous solution.

[0104] Weigh 25.44 g of anhydrous sodium carbonate and dissolve it in deionized water to prepare a sodium carbonate aqueous solution with a concentration of 1.2 mol / L.

[0105] The slurry was added to the reactor, stirring was started, and the reactor was heated to 50°C while stirring at a speed of 300 rpm. While maintaining the above stirring and heating, the nickel nitrate aqueous solution was slowly added to the reactor, and then the sodium carbonate aqueous solution was gradually added dropwise to the reactor to perform an in-situ precipitation reaction for 60 minutes. The precipitation pH value was adjusted to 7.5-8.0. After the precipitation was completed, the material in the reactor was stirred for 3 hours at the above temperature and stirring speed for aging treatment.

[0106] Then stop stirring, filter the material in the reactor, and wash the solid material with deionized water until the washing liquid is neutral. Place the filter cake in an oven, dry it at 120°C for 6 hours, and then put it into a muffle furnace and roast it at 500°C for 3 hours. Grind the solid after roasting to obtain a catalyst precursor. The catalyst precursor is placed in a fixed bed reactor, and a hydrogen and nitrogen mixed gas (mixed volume ratio 1:1) is introduced therein, and the temperature is slowly heated to 450°C by program heating, and heating reduction is continued for 4 hours to obtain the catalyst of Comparative Example 3.

[0107] The XRD spectrum of the catalyst prepared in Comparative Example 3 is as follows: Figure 4 As shown, obvious characteristic diffraction peaks of nickel oxide are observed, indicating that in this catalyst, the nickel-containing component has undergone local aggregation on the support.

[0108] Comparative Example 4

[0109] In this comparative example, the catalyst was synthesized by the following steps, wherein the carrier microstructure used did not meet the definition of the present application.

[0110] Weigh 55.89 g of alumina (specific surface area 150 m 2 / g, and the total pore volume is 0.63cm 3 / g, average pore size of 16.5nm), mixed with 100 ml of ionized water, and stirred thoroughly to form a uniform slurry.

[0111] 58.16 g of nickel nitrate hexahydrate was weighed and dissolved in deionized water to prepare a 1 mol / L nickel nitrate aqueous solution.

[0112] Weigh 25.44 g of anhydrous sodium carbonate and dissolve it in deionized water to prepare a sodium carbonate aqueous solution with a concentration of 1.2 mol / L.

[0113] The slurry was added to the reactor, stirring was started, and the reactor was heated to 50°C while stirring at a speed of 300 rpm. While maintaining the above stirring and heating, the nickel nitrate aqueous solution was slowly added to the reactor, and then the sodium carbonate aqueous solution was gradually added dropwise to the reactor to perform an in-situ precipitation reaction for 60 minutes. The precipitation pH value was adjusted to 7.5-8.0. After the precipitation was completed, the material in the reactor was stirred for 3 hours at the above temperature and stirring speed for aging treatment.

[0114] Then stop stirring, filter the material in the reactor, and wash the solid material with deionized water until the washing liquid is neutral. Place the filter cake in an oven, dry it at 120°C for 6 hours, and then put it into a muffle furnace and roast it at 500°C for 3 hours. Grind the solid after roasting to obtain a catalyst precursor. The catalyst precursor is placed in a fixed bed reactor, and a hydrogen and nitrogen mixed gas (mixed volume ratio 1:1) is introduced therein, and the temperature is slowly heated to 450°C by program heating, and heating reduction is continued for 4 hours to obtain the catalyst of Comparative Example 4.

[0115] The XRD spectrum of the catalyst prepared in Comparative Example 4 is as follows: Figure 4 As shown, obvious characteristic diffraction peaks of nickel oxide are observed, indicating that in this catalyst, the nickel-containing component has undergone local aggregation on the support.

[0116] Embodiment 3:

[0117] In this example, the catalytic performance of the catalysts prepared in the above examples 1-2 and comparative examples 1-4 was characterized, and the results are as follows: Figure 2 , Figure 3 and Figure 4 shown.

[0118] Specifically, a fixed bed microreactor was used in this embodiment, and the loading amount of the catalyst (one of the catalysts prepared in Examples 1-2 and Comparative Examples 1-4) for each reaction was 5 g. A hydrogen-nitrogen mixed gas was charged and heated to 450° C., reduced for 4 h, and then cooled to a reaction temperature of 60° C., and a γ-butyrolactone solution of maleic anhydride was added. The feed volume flow rate was 1.0 ml / min, the volume flow rate of hydrogen was 300 ml / min, the reaction pressure was 0.5 MPa, the reaction temperature was changed between 60-100° C., and the reaction duration was 100 h.

[0119] The results of this series of catalytic reactions are shown in Table 1 below.

[0120] Table 1. Catalytic reaction results using the catalysts prepared in Examples 1-2 and Comparative Examples 1-4

[0121] sample Reaction temperature℃ Maleic anhydride conversion rate (%) Succinic anhydride selectivity (%) Example 1 60 95.5 99.6 Example 2 60 91.4 99.0 Comparative Example 1 60 66.5 99.2 Comparative Example 2 60 66.3 99.3 Comparative Example 3 60 44.8 99.5 Comparative Example 4 60 72.4 98.3 Example 1 80 99.2 99.4 Example 2 80 99.0 99.1 Comparative Example 1 80 95.4 99.1 Comparative Example 2 80 92.2 99.2 Comparative Example 3 80 66.2 99.0 Comparative Example 4 80 91.2 99.3 Example 1 100 99.9 99.2 Example 2 100 99.9 98.4 Comparative Example 1 100 99.0 98.3 Comparative Example 2 100 99.3 98.0 Comparative Example 3 100 94.9 99.0 Comparative Example 4 100 98.7 98.5

[0122] From the catalytic reaction results shown in Table 1, it can be seen that the present invention can conveniently synthesize the catalyst with a simple process and cheap raw materials, and the catalyst exhibits excellent catalytic performance in the catalytic hydrogenation reaction of ethylenically unsaturated carboxylic acids, achieving a raw material conversion rate and target product selectivity that are significantly better than those of the comparative example.

Claims

1. A method for preparing a composite catalyst, the method comprising: Step 1: Disperse the carrier in the first solvent to form a slurry, wherein the carrier is alumina with a specific surface area of ​​200-320 m 2 / g, pore volume 0.5-1.2cm 3 / g, average pore size 5-20nm; Step 2: dissolving a nickel precursor and an optional auxiliary metal precursor in a second solvent to form a precursor solution; Step 3: mixing the slurry and the precursor solution to form a mixed material; Step 4: adding an alkaline precipitant to the mixed material to obtain a catalyst precursor; Step 5: heat-treating and reducing the catalyst precursor to obtain the composite catalyst; The nickel precursor is a water-soluble salt of nickel; The auxiliary metal precursor is a water-soluble salt of one or more elements selected from the group consisting of Group II alkaline earth metals, Group IB elements, Group IIB elements, Group VIB elements, Group VIII transition metals, and rare earth metals.

2. The method according to claim 1, characterized in that In the step 1, the first solvent is water or a water-containing solvent, and the content of the carrier in the slurry is 18-40% by weight based on the total weight of the slurry.

3. The method according to claim 1, characterized in that In the step 2, the second solvent is water or a water-containing solvent, and the concentration of nickel ions in the precursor solution is 0.1-2.5 mol / L; In the case where the precursor solution contains an auxiliary metal precursor, the content of the auxiliary metal precursor in the precursor solution is 0.1 wt % to 0.8 wt % based on the total weight of the precursor solution; The auxiliary metal is selected from one or more of the following: Mg, Cu, Zn, Mo, W, Co, La, Ce.

4. The method according to claim 1, characterized in that In the step 3, the slurry and the precursor solution are mixed in a weight ratio of 1:3 to 4:1; In step 4, the alkaline precipitant is selected from one or more of the following: alkali metal carbonates, alkali metal bicarbonates, alkali metal hydroxides, ammonium carbonate, ammonium bicarbonate, and ammonium hydroxide.

5. The method according to claim 1, characterized in that The heat treatment of the catalyst precursor includes drying at a temperature of 90-150°C for 1-12 hours and calcining at a temperature of 450-700°C for 1-6 hours; The reduction comprises reduction at a temperature of 350-600° C. for 1-8 hours, and a reducing gas and / or an inert gas is used during the reduction process, wherein the reducing gas is selected from hydrogen, carbon monoxide, or a combination thereof, and the inert gas is selected from nitrogen, argon, or a combination thereof.

6. A composite catalyst prepared by the method according to any one of claims 1 to 5.

7. The composite catalyst according to claim 6, characterized in that The composite catalyst comprises a carrier, nickel and an optional promoter metal; Based on 100 parts by weight of the carrier, the content of nickel is 15-40 parts by weight, calculated as nickel oxide; In the case where the composite catalyst contains a promoter metal, the content of the promoter metal is 0.1-5 parts by weight, calculated as oxide, based on 100 parts by weight of the carrier.

8. A method for performing a catalytic hydrogenation reaction, the method comprising performing a catalytic hydrogenation reaction on an unsaturated carboxylic acid or an anhydride thereof containing a carbon-carbon unsaturated double bond in the presence of a catalyst to prepare a saturated carboxylic acid or an anhydride thereof, wherein the catalyst is a composite catalyst as described in any one of claims 6 to 7.

9. The method according to claim 8, characterized in that The unsaturated carboxylic acid or its anhydride containing a carbon-carbon unsaturated double bond is maleic acid or maleic anhydride, and the saturated carboxylic acid or its anhydride is succinic acid or succinic anhydride.

10. The method according to claim 8, characterized in that The catalytic hydrogenation reaction is carried out at a temperature of 60-100°C; The raw material conversion rate of the catalytic reaction is greater than 91%, and the target product selectivity is greater than or equal to 98.4%.